Genetic variability based on isozyme polymorphism among Fusarium oxysporum f. sp. ciceri isolates inciting wilt in chickpea - DEEPA KHULBE, S.K. MUSHRIF* (Indian Phytopathology, 2010)
Biochemical variability among the three isolates of Fusarium oxysporum f. sp. ciceri inciting wilt in chickpea was determined using starch gel electrophoresis technique involving five isozymes. The five isozymes tested in electrophoretic studies viz. Glucose-6-Phosphate dehydrogenase (G6PDH), 6 Phosphogluconate dehydrogenase (6PGDH), Malate dehydrogenase (MDH), Isocitrate dehydrogenase (IDH) and Superoxide dismutase (SOD) gave distinct isozyme profiles. These studies indicated that the Bangalore isolate differed from Gulbarga and Race-1(a designated race from ICRISAT) isolates. It was also noticed that the Gulbarga isolate was genetically closer to the Race-1 isolate. Bangalore isolate seems to be a novel evolving race of F. oxysporum f. sp. ciceri.